TIPS MERAIH UNTUNG BERLIPAT GANDA DALAM BISNIS RITEL - -, Lamidi - (Universitas Slamet Riyadi, 2011)
ABSTRACT Any business owner would want the maximum benefit from his efforts, so did the retail business. This article examines 12 Tips to manage the retail business to achieve profits doubled. “Tips Achieve Good thing doubled in Retail Business